Smoking Status and the Incidence of Pancreatic Cancer Concomitant With Intraductal Papillary Mucinous Neoplasm. Issue 4 (April 2017) - Nakagawa, Takashi; Masuda, Atsuhiro; Toyama, Hirochika; Shiomi, Hideyuki; Zen, Yoh; Sofue, Keitaro; Takenaka, Mamoru; Kobayashi, Takashi; Yagi, Yosuke; Yamanaka, Kodai; Yoshida, Masaru; Arisaka, Yoshifumi; et al.
Abstract : Objectives: The effect of smoking status on the incidence of pancreatic ductal adenocarcinoma (PDAC) concomitant with intraductal papillary mucinous neoplasm (IPMN) has not been clarified. This study investigated the association of smoking status with PDAC concomitant with IPMN. Methods: The subjects were 124 consecutive patients undergoing resection of IPMNs (intraductal papillary mucinous adenoma (IPMA): N = 77, invasive IPMN: N = 31, and PDAC with IPMN: N = 16) between April 2008 and October 2015. The associations between smoking status (never/former/current smoker) or cumulative pack-years (0–19/20–39/≥40) and the incidence of PDAC concomitant with IPMN or invasive IPMN were evaluated. Results: Current smoking, not former smoking, was associated with the incidence of PDAC concomitant with IPMN (PDAC with IPMN vs IPMN alone; P = 0.004, PDAC with IPMN vs IPMA; P = 0.004, PDAC with IPMN vs invasive IPMN; P = 0.04, respectively), but not that of invasive IPMN (invasive IPMN vs IPMA; P = 0.85). Cumulative pack-years were higher in patients who had PDAC concomitant with IPMN than in patients with invasive IPMN ( P = 0.04). Cumulative pack-years were not associated with smoking status (current vs former). Conclusions: Current smoking, not former smoking, was associated with the incidence of PDAC concomitant with IPMN. Cessation of smoking may be recommended for patients with IPMN.